EFFECTS OF COOPERATIVE LEARNING METHOD ON ACADEMIC ACHIEVEMENT AND RETENTION OF STUDENTS IN BASIC TECHNOLOGY IN OYO STATE (NAU Journal of Technology and Vocational Education, 2024)
This study was necessitated by persistent declining in the academic achievement inBasic Technology in public examinations by junior secondary school students. Thestudy determined the effects of cooperative learning method (CLM) on academicachievement and retention in Basic Technology in Oyo State. Three researchquestions guided the study and three null hypotheses were tested at 0.05 level ofsignificance. The population of the study was 19,892 JSS II Basic Technology studentsin Oyo State. The purposive sampling technique was used to select 114 students forthe study. Pre-test, Post-test and non-equivalent group quasi-experimental researchdesign was used for the study and the instrument for data collection was BasicTechnology Achievement Test (BTAT) which was validated by three experts. Areliability correlation coefficient of 0.82 was obtained for the test items using test retest and Pearson Product Moment Correlation. Mean was used to analyse datarelating to the research questions while analysis of covariance (ANCOVA) was usedto test the hypotheses at 0.05 level of significance. Findings revealed that studentstaught Basic Technology using CLM performed better with higher post-test scoresthan those taught using conventional teaching method (CTM). Findings also indicatedthat retention mean score of students taught Basic Technology using CLM was higherthan those taught using CTM, both high and low achieving students were favoured bythe use of CLM but low achieving students were slightly favoured by the use of CLMbut low achieving students were slightly favoured more. The interaction effect ofteaching methods and gender was not significant on students’ academic achievementand retention in Basic Technology. Hence, it was recommended among others thatschool administrators should provide opportunities for in-service training for BasicTechnology teachers in order to equip them with competencies needed in the use ofCLM for teaching the subject.
Keywords: Cooperative learning, achievement, retention, Oyo State